Concepções de trabalho para pessoa idosa - Costa, Sônia Mara Gusmão (2018)
Introduction: Population aging has been happening in the world rapidly and intensely, especially in developing countries, such as Brazil. Changes in demographic profile result in new dimensions and social configurations, such as the continuation or return of the elderly to paid or informal activities after retirement. Objectives: to highlight in the scientific literature studies on the elderly in the labor market; know the conceptions about work for the elderly. Method: An exploratory study of a qualitative approach, with a non - probabilistic sample of convenience, performed with 370 elderly participants of both sexes, divided into two groups (Group 1 - year 2013, n = 260 and Group 2 - year 2018, n = 110) in the municipality of João Pessoa / Paraíba / Brazil. The present study was approved by the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraíba, under the opinion of: 2,190,153, duly registered in the Brazil platform (CAAE: 67103917.6.0000.5188). All criteria established by Resolution 466/12 of the National Health Council (CNS) were complied with. The empirical data originated from a semistructured interview with two sections: the first one comprises the Free Word Association Test (TALP) with the word inductor: "Work for the elderly" and the second section the semi-structured interview that includes the data sociodemographic. The collected data were organized in a corpus according to the inductive word and processed using the software IRaMuTeQ® and the sociodemographic database were processed by SPSS 20.0. Results: The results correlate with each other, making it possible to identify 4 categories common to both groups (2013 & 2018): positive expectations of work for the elderly 36%; conceptions of work for the elderly - 19.4%; negative expectations of work for the elderly 31.5%; types of jobs for the elderly - 13.1%. Conclusions: the study shows that conceptions of work for the elderly are generally associated with both continuity and reintegration in the formal or informal labor market, as well as their re-signification.